2010
DOI: 10.1002/jpln.201000099
|View full text |Cite
|
Sign up to set email alerts
|

Effects of three commercial rootstocks on mineral nutrition, fruit yield, and quality of salinized tomato

Abstract: Tomato (Solanum lycopersicum Mill. cv. Belladona F1) plants were either self‐rooted, self‐grafted, or grafted onto the commercial rootstocks “Beaufort”, “He‐Man”, and “Resistar” and grown in a recirculating hydroponic system. Three nutrient solutions differing in NaCl‐salinity level (2.5, 5.0, and 7.5 dS m–1, corresponding to 0.3, 22, and 45 mM NaCl) were combined with the five grafting treatments in a two‐factorial (3 × 5) experimental design. At the control NaCl level (0.3 mM), fruit yield was not influenced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
51
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 40 publications
6
51
0
Order By: Relevance
“…This objective would enhance crop yield under organic production (Farias et al 2013) and nutrient stress (Savvas et al 2010;King et al 2010), increasing agriculture sustainability. Noteworthy, Savvas et al (2011) reported that grafting onto three commercial tomato rootstocks, significantly reduced the leaf Mg concentration resulting in clear Mg-deficiency symptoms of salinized tomato. Our results provide information on QTL positions at four chromosomes that could be used to improve the scion Mg content under moderate salinity through a proper rootstock selection.…”
Section: Discussionmentioning
confidence: 99%
“…This objective would enhance crop yield under organic production (Farias et al 2013) and nutrient stress (Savvas et al 2010;King et al 2010), increasing agriculture sustainability. Noteworthy, Savvas et al (2011) reported that grafting onto three commercial tomato rootstocks, significantly reduced the leaf Mg concentration resulting in clear Mg-deficiency symptoms of salinized tomato. Our results provide information on QTL positions at four chromosomes that could be used to improve the scion Mg content under moderate salinity through a proper rootstock selection.…”
Section: Discussionmentioning
confidence: 99%
“…Boludo F1 (Seminis Vegetable Seeds Ibérica S.A., Barcelona, Spain) used as the scion to search for tolerant rootstocks under K deficiency (Albacete et al, 2015b). Grafting was performed using the splicing method at the two to three true leaf stages where the scion was attached at the first node of the rootstock (Savvas et al, 2011). One month later (25th September 2012), grafted plants were transferred to a commercial greenhouse located in the Mazarrón tomato producing area (37°33′19.96″ N, 1° 22′53.95″ W) and cultivated in a semi-hydroponic system using sand as substrate.…”
Section: Methodsmentioning
confidence: 99%
“…Grafting is a technique adopted to increase the yield and tolerance to several soilborne pathogens in vegetables since 1920 (Lee, 1994). Besides the advantages on pathogen control, this technique is worldwide diffused for many crops to improve yield (Bletsos, 2003;Cassaniti et al, 2011), fruit quality (Savvas et al, 2011) and tolerance to a variety of abiotic stresses (Rivero et al, 2003;Giuffrida et al, 2013). It has been reported that tomato grafted plants show higher yield than ungrafted ones (Martínez-Rodríguez et al, 2002), and that their growth is dependent upon the interaction between rootstock and scion (e.g.…”
Section: Introductionmentioning
confidence: 99%